Design and Construction of Broccoli (Brassica Oleracea, L.) Storage Box Using Thermoelectric Technology - Bertung Suryadharma; Andrew Setiawan Rusdianto; Zahra Zuhriasa (Newinera Publisher, 2021)
Fresh vegetables determine the selling price of the product, so traders must be careful in storing vegetables to keep them staying fresh. Therefore, we need a vegetable storage device that can maintain the specified temperature, can lower the temperature, and is effective. The solution used is to design a vegetable storage device using thermoelectric technology that can maintain temperature. This research was conducted in May-June 2021 and was carried out at the Laboratory of Agroindustrial Technology and Management, Faculty of Agricultural Technology, University of Jember. The tools used for research are Laptop and Arduino IDE. Materials used in this research are Breadboard, Arduino Uno, Peltier TEC1-12706, DS18B20 Sensor, Jumper Cable, Heatsink, Fan, 1 channel Relay, Power supply, LCD, and Styrofoam Box. The tool that had been tested for performance was then tested by operating the cooler box. Testing the tool aimed to determine the ability of the cooler to reach the desired temperature. Based on the functionality validation test, it was found that X=1 which means the cooler in the broccoli vegetable storage box is declared to be functioning properly. The DS1820B sensor used in this study got a % error value of 1.19% which means the temperature sensor can work well. The cooler box has the fastest ability to reach a temperature of 15oC in 10 minutes 09 seconds with a power of 12 W. The cost required for a cooler for 1 (one) day is cheaper than a showcase, which only costs Rp. 2,336.